Differentiation of Croatian companies by benefits as an aspect of employee compensation - Čurčija, Slobodan; Fabijanac, Mateja (Crisis Management Days, 2025)
Abstract The purpose of this paper is to investigate the differences in employee benefits compensation in Croatian companies during the COVID-19 pandemic and after its ending. Accordingly, an empirical study was conducted to analyze these differences, encompassing a population of employees from the public and private sectors in the Republic of Croatia. In this regard, the research sample consisted of seventy-two respondents aged 18 to over 60 years. The research results are divided into four sections. The first section uses descriptive statistics to outline the general and demographic characteristics of the survey respondents. The second section presents findings on employee satisfaction with the benefits offered by their current employer and the impact of the COVID-19 pandemic on changes in benefit options. The study concludes with an overview of respondents' opinions on the current landscape of available benefits in Croatian companies or by their employers. The analysis confirmed that the pandemic initiated changes in the structure of benefit programs. Furthermore, expanding the range of benefit options was found to positively influence overall employee satisfaction. Moreover, most respondents consider the availability of benefits to be a crucial factor when choosing an employer. However, a notable deficiency in flexible benefit programs was identified, underscoring the need to enhance and expand compensation offerings to include such benefits. Consequently, Croatian employers should consider adapting their benefit programs to more effectively meet employees' individual needs in the post-pandemic period. One of the limitations of the study is its relatively small sample size. Introduction The COVID-19 pandemic has brought substantial changes to various aspects of business, including how companies manage human resources and structure compensation systems. In contemporary business environments, benefits have become an increasingly important element of compensation, representing indirect financial rewards provided by employers in addition to regular salaries. This trend is a result of accelerated changes in the labor market, where human resources have assumed a key role in achieving a company’s competitive advantage. Consequently, employers are increasingly focused on offering benefits that attract and retain quality employees while simultaneously enhancing their satisfaction and work efficiency. Satisfied employees perform better, contributing to the organization's overall success. The introduction of additional benefit aspects during the pandemic allowed companies not only to address the specific needs of employees but also to maintain workforce motivation and satisfaction under crisis conditions. Many of these newly introduced elements of benefits packages have remained relevant even after the pandemic, underscoring their importance for research and analysis. Therefore, the primary intent of this study stems from recognizing the pandemic's impact on the priorities of both employers and employees as well as the need to understand employee motivation and satisfaction. Based on this, the research subject is to analyze the structuring and implementing benefits as a form of employee compensation in Croatian companies during and after the COVID-19 pandemic, particularly in 2024. Following the research subject, the basic hypothesis has also been formulated, and it reads as follows: The COVID-19 pandemic triggered changes in the availability of employee benefits in Croatian companies. Data collection for this study utilized a combination of primary and secondary research. The primary research was conducted through a survey of employees in Croatian companies to gather insights into their attitudes toward benefits during the COVID-19 pandemic and in 2024. Additionally, this research provided an overview of Croatian companies' practices and identified differences in the application of benefits during the pandemic and in the following years. In connection with this and to apply empirical research, a survey questionnaire was developed consisting of 28 questions organized into four sections. The survey was administered online with a sample of 72 respondents between mid-June and late August 2024. The collected data were analyzed using description, analysis, synthesis, comparison, and generalization methods. Secondary research consisted of reviewing professional and academic literature on human resource management, employee motivation, and compensation systems, with a particular focus on benefits. The empirical findings supported the primary hypothesis, with 59.7% of respondents indicating that the COVID-19 pandemic had initiated changes in employee benefit offerings within Croatian companies, while 19.4% disagreed. Furthermore, 32% of respondents reported that they still have access to benefits introduced during the pandemic whereas 15% expressed dissatisfaction in this regard. However, results regarding access to flexible benefit programs were notably disappointing, with only 9.7% of respondents indicating availability, while 90.3% reported the absence of such options.